The Chromosomes of Dictyostelium Giganteum - Kumar Rishikesh; S. Kulshreshtha Pooja; Nanjundiah Vidyanand; S. Kadandale Jayarama (Journal of Chromosomes, 2024)
As a first step towards clarifying the basis of the cooperation and conflict seen in chimeric binary mixes of Dictyostelium giganteum, we examined the karyotype of six natural isolates. All six had 5 haploid chromosomes. No meiotic figures were seen. Fluorescence in-situ hybridization was carried out using conserved D. discoideum centromeric DNA sequences as probes. From it, we infer that two chromosomes are sub-metacentric, one is metacentric and two are telocentric.
Keywords: Chromosome